Respon Tumbuhan Terhadap Pencemaran Polusi Udara di Kawasan Kota Binjai - Muhammad Faisal; Nazwa Ramadhona; Dwi Khairani; Rimsa Desela putri br Panjaitan; Anjelita Sinaga (Politeknik Kampar, 2024)
Abstract : This study aims to analyze the response of plants to air pollution in the Binjai City area, which faces increased urbanization and industrial activities. The main focus of this research is the impact of pollutants, such as carbon monoxide (CO), nitrogen dioxide (NO2), and sulfur dioxide (SO2), on the physiology and morphology of plants, including stomatal damage, chlorophyll reduction, and leaf growth. Data were collected through field observations and laboratory analyses of local plant species exposed to urban and suburban environments. The results indicate that air pollution levels negatively correlate with plant health, as observed in the reduction of photosynthesis and biomass production. This study is expected to provide recommendations for environmental conservation and air quality management in urban areas.